Leiomyoma With Ossification- An Unusual Case Presentation - Phom, P Meilung; Thanka, J; Priyadarshini, R.S Gayathri (Journal of Neonatal Surgery, 2025)
Uterine leiomyomas are common benign smooth muscle tumours, yet the occurrence of ossification within these tumours remains a rare and intriguing entity. This case explores the clinical, radiological and pathological features of leiomyoma with ossification. Radiologically, these entities often present as heterogeneous masses with calcifications. Histopathologically, the presence of mature bone within the smooth muscle tumour characterizes this variant, though the precise etiology remains unclear. Leiomyoma with ossification represents a unique subset within the spectrum of benign smooth muscle tumours, necessitating a multidisciplinary approach for accurate diagnosis and appropriate management for optimal patient care and outcome